If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(12x + -3) + -3(1 + -3x) = 6(x + -10) Reorder the terms: 2(-3 + 12x) + -3(1 + -3x) = 6(x + -10) (-3 * 2 + 12x * 2) + -3(1 + -3x) = 6(x + -10) (-6 + 24x) + -3(1 + -3x) = 6(x + -10) -6 + 24x + (1 * -3 + -3x * -3) = 6(x + -10) -6 + 24x + (-3 + 9x) = 6(x + -10) Reorder the terms: -6 + -3 + 24x + 9x = 6(x + -10) Combine like terms: -6 + -3 = -9 -9 + 24x + 9x = 6(x + -10) Combine like terms: 24x + 9x = 33x -9 + 33x = 6(x + -10) Reorder the terms: -9 + 33x = 6(-10 + x) -9 + 33x = (-10 * 6 + x * 6) -9 + 33x = (-60 + 6x) Solving -9 + 33x = -60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 33x + -6x = -60 + 6x + -6x Combine like terms: 33x + -6x = 27x -9 + 27x = -60 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + 27x = -60 + 0 -9 + 27x = -60 Add '9' to each side of the equation. -9 + 9 + 27x = -60 + 9 Combine like terms: -9 + 9 = 0 0 + 27x = -60 + 9 27x = -60 + 9 Combine like terms: -60 + 9 = -51 27x = -51 Divide each side by '27'. x = -1.888888889 Simplifying x = -1.888888889
| X/3+3=18 | | -2d+32=0 | | 3k-1=11k | | 5y(3+4)=6y+1 | | -1/100g+60 | | -5h-7=-127 | | -5h-7=-100 | | (3/4)*x+14=-38 | | -10x+16=3x-2 | | 10x+16=3x-2 | | x/8-20=85 | | 2(x-3)+3(4-x)=5 | | 13x-30=21x-14 | | 10+n/6=7 | | -10+x/5=8 | | 2.4+x/2=8 | | .7z+1.9+0.1=5.5-0.4z | | -4m+27=63 | | -2+13q=50 | | 108=12p-32 | | 8-1/3x=12 | | 25n+50=-1500 | | -3/4x=7 | | Y=x^4-2x^3 | | 3w+15=65 | | 25-4/10d=0 | | -30-(-83)= | | 34=13x+(-18) | | -3/4m+9.5=4.75 | | 4x+18=66 | | -3/4m+9.5=0 | | y^2-11y+14=0 |